2008
DOI: 10.1103/physrevd.78.123508
|View full text |Cite
|
Sign up to set email alerts
|

Quantum particle production at sudden singularities

Abstract: We investigate the effects of quantum particle production on a classical sudden singularity occurring at finite time in a Friedmann universe. We use an exact solution to describe an initially radiation-dominated universe that evolves into a sudden singularity at finite time. We calculate the density of created particles exactly and find that it is generally much smaller than the classical background density and pressure which produce the sudden singularity. We conclude that, in the example studied, the quantum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 32 publications
4
39
0
Order By: Relevance
“…This means that the sudden singularity cannot be avoided from conformal anomaly contribution. This results perfectly agrees with that found in [35,40], where in the framework of GR it has been shown that sudden singularity cannot be avoided both from particle production and conformal anomaly. However, it appears that the avoidance of the sudden singularity could come from the matter contribution, due to the same exponent for R and g T .…”
Section: Conformal Anomaly Near the Sudden Singularitysupporting
confidence: 92%
“…This means that the sudden singularity cannot be avoided from conformal anomaly contribution. This results perfectly agrees with that found in [35,40], where in the framework of GR it has been shown that sudden singularity cannot be avoided both from particle production and conformal anomaly. However, it appears that the avoidance of the sudden singularity could come from the matter contribution, due to the same exponent for R and g T .…”
Section: Conformal Anomaly Near the Sudden Singularitysupporting
confidence: 92%
“…They can also be shown to be stable to small perturbations using standard perturbation theory [11], and one can adapt the arguments above to show they form in expanding, homogeneous universes with large anisotropies. They are even stable to quantum corrections since one can construct examples where the divergence only occurs at an arbitrarily high order of the scale factor derivative [12,13]. This is in contrast to most other examples of weak singularities discovered so far.…”
mentioning
confidence: 85%
“…[12][13][14][15][16][17][18] and for discussions of quantum effects see Refs. [19,20]. Sudden singularities stand in stark contrast to big rip singularities as they are much weaker.…”
Section: Introductionmentioning
confidence: 99%